Downhill nach einem Theaterstück von Constance Collier und Ivor Novello - Hitchcock, Alfred; MacDonnell, Claude L.; Novello, Ivor; Webster, Ben; McKinnel, Norman (Alfred Hitchcock - The Early Years, 2003)
"Downhill", made at Gainsborough Studios in 1927, was written by its star, Ivor Novello in collaboration with Constance Collier. Released the United States as "When Boys Leave Home", it was the story of a young boy accused of stealing at his school. Although completely innocent, he is expelled from school. His father, outraged at what the boy has supposedly done, rejects him, and boy leaves home. He goes to Paris, has an affair with an actress, and eventually comes home to his parents. They are remorseful after learning their son was innocent. Hitchcock experimented with some dream sequences by shooting them in super-impositions and blurred images; this was unlike the work of most other directors of that time except possibly the early work of Rene Clair (Entr' Acte) and Abel Gance (La folie de Docteur Tub, Napoleon). [www.britmovie.co.uk]